Leveraging Artificial Intelligence for Digital Marketing: Insights from SHEIN for VMS Industry - KHERBACHI , Sonia; BENKHIDER , Naima; KEDDARI , Nassim (Dirassat Journal Economic Issue, 2024)
In the current global landscape, where technology-driven data penetration is the hardcore of digital marketing, Artificial Intelligence has gained paramount importance. This paper explores artificial intelligence applied to digital marketing practices through associated technologies. Through qualitative and quantitative approaches, we aim to propose research directions addressing AI challenges firms encounter in marketing. A qualitative interview with VMS Industry’s marketing manager and a quantitative analysis of Hugging Face’s implementation in SHEIN’s marketing activities were conducted. The results have revealed that using Artificial Intelligence fundamentally redefines how firms’ approach and succeed in their digital marketing practices. SHEIN’s experience in integrating artificial intelligence into its marketing practices could be an emerging solution for gaining visibility on the web. For the VMS Industry, the results have confirmed that Artificial Intelligence’s selective and targeted use in personalizing interactions with customers and creating visual and textual content is optimized.